EXTERNAL PARASITISM IN GUINEA PIGS (Cavia porcellus) REARED IN FAMILY-COMMERCIAL FARMS DURING THE RAINY AND DRY SEASONS IN OXAPAMPA, PERU - Robles N., Katherine (2014)
The aim of the study was to determine the frequency of external parasites in guineapigs (Cavia porcellus) during the rainy and dry seasons in family-commercial farms inOxapampa, Pasco, Peru. Also, aimed to identify the ectoparasites and to determine theassociation between seasons and the presence of external parasites. A total of 230 animals were evaluated per season. Ectoparasites were collected using three techniques: skinscraping, transparent tape, and fine comb. The frequency of parasitism was 70.9 ± 5.9 and83.0 ± 4.9% for the rainy and dry seasons respectively. Five species of Acariformes andthree species of Phthiraptera were identified, and the most frequent were Chirodiscoidescaviae and Gliricola porcelli. Significant association was found between the season ofthe year and the presence of external parasitism (p<0.05).